LITERARY MEMES AS BIBLIOTHERAPY FOR FILIPINO ESL PRESERVICE TEACHERS’ EMERGENCY REMOTE LEARNING - Bañez, Richard Mendoza (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
The COVID-19 pandemic led to a swift transition to emergency remote teaching, impacting students and educators’ well-being. To address these challenges, literary memes emerged, combining literary references with humour or poignant commentary, engaging students, and conveying meaningful insights or coping strategies. Despite their prevalence, their efficacy as bibliotherapy tools remains underexplored. This study investigated the potential of literary memes in promoting well-being and enhancing the learning experience during times of crisis. Focused on 64 English as a Second Language (ESL) Filipino preservice teachers, the study explored their preferences and perceived value of literary memes, ascertaining their exposure and assessment of this emerging literary genre as potential bibliotherapy. Qualitative data underwent thematic analysis, while quantitative data underwent statistical analysis, including measures such as mean, standard deviation, Pearson correlation coefficient (r), and t-tests. Findings indicated that ESL preservice teachers preferred memes creatively linked to literature, maintaining a moderate level of exposure, using them to forge emotional connections with peers and family. These memes, abundant in literary references, provided entertainment and moderately contributed to bibliotherapy, as confirmed by the values of Pearson r and t-tests, calling for their integration into ESL teacher education programs to foster engagement and well-being among preservice teachers.